Beyond classroom English activities to generate interest in English among tertiary students / Alice Shanthi and Zuraidah Jaafar - Shanthi, Alice; Jaafar, Zuraidah (Universiti Teknologi MARA, 2020)
In this article, we present a study aimed to explore the attitude, interest and perception of students learning English language beyond the classroom using a list of activities such as Readers Theatre, Storyboard, Academic Explorace, Spell it right and Melodies of Pilah. A survey was conducted involving 466 students from different faculties who were taking English proficiency courses at diploma and degree levels at a local university. The findings indicate that both male and female students had a positive degree of interest and attitude toward the English activities carried out beyond the classroom. The popular activities were Readers Theatre and Melodies of Pilah (group singing). The study also indicated that students preferred group activities compared to individual activities. Based on the findings, it is recommended that students should be allowed to explore English materials independently beyond classrooms where language learning takes place implicitly. The study found that the success of English learning activities carried out beyond the confines of the classroom can generate interest among students to learn the language. The success of English activities carried out beyond classrooms can be assessed by students’ ability to complete the task assigned (the end-product) rather than the processes involved in completing the task.